Tradisi Babako pada Masyarakat Minang Kelurahan Bungo Pasang Kecamatan Koto Tangah Kota Padang Sumatera Barat - Aulia Atika Putri; Ashaluddin Jalil (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Culture is another word for tradition. Traditions are community habits that have been carried out from generation to generation based on the cultural values ​​of the community concerned. The study wants to know: 1) What is the process of implementing the Babako Tradition in the Minang Community and 2) What are the values ​​contained in the Babako Tradition in the Minang Community. Activity is a form of culture as a patterned action by humans in that society and this form is often known as a social system. The social system consists of human activities that interact with each other, adapt to each other by using eye contact to interact, and socialize with other people. The type of research used in this research is Descriptive Qualitative. The research subjects determined by the researcher using the purposive technique are a technique for determining subjects with conditions and criteria that have been determined by the researcher and have been carried out with considerations in accordance with the research objectives. The results of the discussion found that the Babako Tradition is included in the Customs which has 5 stages in the implementation process, namely 1) Starting from preparing and putting on clothes at the bako house. 2) The procession of the procession (Baarak Bako). 3) The arrival of the bako group and the bride and groom. 4) Hair cutting (Bacukua). 5) Ring installation. This research was conducted in Bungo Pasang Village, Koto Tangah District, Padang City, West Sumatra.